PENGARUH BOOK TAX DIFFERENCE, ARUS KAS OPERASI TERHADAP LIKUIDITAS PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Nurmala; Malahayati, Rina; Yunita Altin Natanael (LPPM Universitas Ibnu Sina, 2024)
This study aims to examine and determine the effect of book tax difference and operating cash flow on the liquidity. In addition, this study also aimsto test whether a variable book tax differences and current operation on the liquidity. The number of population used is 9 companies and the place used in this study are companies pharmacy listed on the Indonesian stock exchange during the 2018-2022 period. Data analysismethod uses multiple linier regression with the help of the 2020 spss program. The results of the study show that either jointly or partially, the independen variable influential the dependen variable.